2021
DOI: 10.1016/j.omtn.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

VPS33B modulates c-Myc/p53/miR-192-3p to target CCNB1 suppressing the growth of non-small cell lung cancer

Abstract: VPS33B is reported to be a tumor suppressor in hepatocellular carcinoma, nasopharyngeal carcinoma, colon cancer, and lung adenocarcinoma. Here, we observed that reduced VPS33B protein level was an unfavorable factor that promoted the pathogenesis of non-small cell lung cancer (NSCLC) in clinical specimens. We achieved lentivirus-mediated stable overexpression of VPS33B in NSCLC cells. Increased VPS33B reduced cell cycle transition and cell proliferation of NSCLC cells in vivo and in vitro. Knocking down VPS33B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…But, the mechanism of PRC1 in cancer is still unclear. CCNB1 is a regulatory protein involved in mitosis and a critical cell cycle regulator of the G2/M checkpoint [30]. Previous studies have reported that CCNB1 could participate in oncogene pathways among many kinds of cancers, such as BC and colorectal cancer [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…But, the mechanism of PRC1 in cancer is still unclear. CCNB1 is a regulatory protein involved in mitosis and a critical cell cycle regulator of the G2/M checkpoint [30]. Previous studies have reported that CCNB1 could participate in oncogene pathways among many kinds of cancers, such as BC and colorectal cancer [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between VPS33B and T2D is unknown, although VPS33B is expressed in pancreas tissue, and encodes Vascular Protein Sorting-associated protein 33B [ 32 ]. The function of VPS33B refers to intracellular protein trafficking and membrane fusion mechanisms [ 33 ]. It also plays critical roles in bile acids metabolism [ 34 ], which could contribute to the regulation of glucose homeostasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MYC gene has been confirmed to be a key oncogene affecting many malignant tumors [ 22 ]. Many related studies have reported that MYC plays an important role in the development of LUAD.…”
Section: Discussionmentioning
confidence: 99%